The Role of Entrepreneurial Orientations in Achieving Strategic Status- an Empirical Study in Private Commercial Banks in Baghdad - Awni, Saadiyah Owaid (International Journal of Indonesian Business Review, 2025)
Purpose –The research aims to form comprehensive intellectual visions and clear perceptions about the relationship between entrepreneurial orientations and achieving strategic status in light of the major changes in the business environment and the knowledge-based economy, in an attempt to generalize the model and the extent of its applicability in the Iraqi environment Methodology/approach – The research relied on the descriptive analytical approach by deriving hypotheses and testing them based on a questionnaire distributed to (92) senior management, employees, and managers of departments and divisions in a sample of private commercial banks in Baghdad. To analyze the data, statistical means and tools were used to analyze the data through statistical programs (SPSS), (AMOS 23). Findings – The results showed the validity of all the main and sub-hypotheses of the research. Based on that, a set of conclusions were formulated that recommend the necessity for private commercial banks to increase investment in entrepreneurial trends, renew ideas, and develop banking services provided to customers, as well as keep pace with developments in global banking services provided in developed countries. Novelty/value – The research is original in its attempt to generalize the proposed model and assess its applicability to the Iraqi private banking sector, an area that has received limited attention in previous studies. By investigating the role of entrepreneurial orientations in enhancing strategic status, the study addresses a gap in the literature regarding how such orientations can be effectively utilized within the specific socio-economic and cultural context of Iraq.